FUNCTIONALITIES OF FRBR-BASED INFORMATION VISUALISATION IN LIBRARY BIBLIOGRAPHIC RECORDS (Journal of Digital System Development, 2023)
This study explores the potential of the Functional Requirements for Bibliographic Records (FRBR) model as a tool for information visualisation in bibliographic control. This research aims to investigate how FRBR can be employed to enhance the visualisation of bibliographic data, examine the impact of FRBR on information organisation and retrieval, and identify and analyse the challenges associated with FRBR implementation. The researchers applied thematic analysis, where the study has three main phases. The process started with designing the review and then conducting the review. Lastly, analyse and organise the review. The analysis of the study is gained through reviewing existing literature through thematic analysis; thus, three main aspects, which contain four themes, have been presented within the study. It is important to note that the study makes a significant contribution as it focuses on library interface interaction along with the stress on relationships of entities between static and interactive bibliographic records.